Socio-demographic Profile and Complications of Measles in Children: A Hospital Based Study - Rahat, Farhana; Abiduzzaman, AFM; Khanam, Morsheda; Choudhury, Ahmed Murtaza (Dhaka Shishu (Children) Hospital Journal, 2023)
Background: Measles is a self-limited viral disease. But it can cause serious complications in young children and still remains as an important cause of mortality and morbidity in under five children worldwide. Objectives: The aim of the study was to determine the complications of measles in hospitalized children and to observe the socio-demographic profile of them. Methods: A prospective observational study was conducted in Dr M R Khan Shishu Hospital and Institute of Child Health from March to December 2019. Children of 6 months to 10 years who came with signs and symptoms of measles according to the case definition criteria by WHO, like fever with maculopapular rash associated with cough, runny nose and conjunctivitis were included in the study. Their sociodemographic profile was recorded and different complications were noted. Results: A total of 86 children suffering from measles with different complications were admitted during the study period. They were from 6 months to 10 years. Among them 59% were below 1 year, 80% were below 4 years and 94% were less than 7 years. Thirty eight percent children were from lower and thirty percent from middle socioeconomic background. Pneumonia was the main complication found in 62(72%) cases followed by diarrhea 28(32%), oral ulcer 26(30%), croup 5(6%) and febrile seizure 4(4.6%). Most (79%) of the children, had normal nutritional status. Among 62 children aged 9 months to 10 years, only 16(26%) received 2 doses of measles vaccine, 14(23%) only the first dose and 32(52%) was not vaccinated at all. Vaccination rate was poor (27%) in low socio-economic condition. The mortality rate was 1(1.16%). Conclusion: About 60% of the children, suffering from measles, were less than one year of age. Fifty nine percent of them were not vaccinated. The children developed complications like pneumonia, diarrhea, oral ulcers etc. Vaccination status was poor in low socio-economic condition. So, awareness should be created about timely vaccination of measles. DS (Child) H J 2022; 38(2): 84-88